Mycoplasma Chromosomal Transfer: A Distributive, Conjugative Process Creating an Infinite Variety of Mosaic Genomes - Dordet-Frisoni, Emilie; Faucher, Marion; Sagné, Eveline; Baranowski, Eric; Tardy, Florence; Nouvel, Laurent Xavier; Citti, Christine (Frontiers in Microbiology, 2019)
The capacity of Mycoplasmas to engage in horizontal gene transfers has recently been highlighted. Despite their small genome, some of these cell wall-less bacteria are able to exchange multiple, large portions of their chromosome via a conjugative mechanism that does not conform to canonical Hfr/oriT models. To understand the exact features underlying mycoplasma chromosomal transfer (MCT), extensive genomic analyses were performed at the nucleotide level, using individual mating progenies derived from our model organism, Mycoplasma agalactiae. Genome reconstruction showed that MCT resulted in the distributive transfer of multiple chromosomal DNA fragments and generated progenies composed of a variety of mosaic genomes, each being unique. Analyses of macro- and micro-events resulting from MCT revealed that the vast majority of the acquired fragments were unrelated and co-transferred independently from the selection pressure. Housekeeping and accessory genes were equally affected by MCT, with up to 35 CDSs being gained or lost. This efficient HGT process also created a number of chimeric genes and genetic micro-variations that may impact genes regulation and/or expression. Our study unraveled the tremendous plasticity of the small mycoplasma genome and point towards MCT as a major player in diversification and adaptation to changing environments, offering a significant advantage to these minimal pathogens.